PENERAPAN MODEL VISUALIZATION, AUDITORY, KINESTHETIC (VAK) DENGAN MULTIMEDIA DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS IV SD NEGERI GADUNGREJO TAHUN AJARAN 2015/2016 - Mahmudah, Nisa (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Visualization, Auditory, Kinesthetic (VAK) Model Using Multimedia in Improving Social Science Learning for the Fouth Grade Students of SD Negeri Gadungrejo in the Academic Year of 2015/2016. The objectives of this research to improve social science learning. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection. Sources of data were derived from students and teachers. Techniques of collecting data were observation, interview, and test. The result of the research showed that the application of VAK model using multimedia can improve social science learning by the increase of learning mastery of students in the first cycle 69.23%, in the second cycle 93.75%, and in the third cycle 95%. The problems encountered in the application of VAK using multimedia are the teacher lacks in motivating students to ask questions actively and the teacher has difficulty to encourage students to deliver conclusion individually. Solutions for these problems are the teacher gives opportunity to students to ask difficult questions and the gives extra time for students to think so that be confident in concluding learning materials. Keywords:VAK, multimedia, learning, social science, social problem Abstrak : Penerapan Model Visualization, Auditory, Kinesthetic (VAK) dengan Multimedia dalam Peningkatan Pembelajaran IPS pada Siswa Kelas IV SD Negeri Gadungrejo Tahun Ajaran 2015/2016. Penelitian ini bertujuan  untuk meningkatkan pembelajaran IPS. Penelitian tindakan kelas kolaboratif ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari dua pertemuan dengan tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Sumber data berasal dari siswa dan guru. Teknik pengumpulan data menggunakan observasi, wawancara, dan tes. Hasil penelitian menunjukkan bahwa model VAK dengan multimedia dapat meningkatkan pembelajaran IPS yang dapat dilihat dari peningkatan ketuntasan hasil belajar siswa siklus I 69,23%, siklus II 93,75%, dan siklus III 95%. Kendala dalam penerapan model VAK dengan multimedia yaitu; guru kurang memotivasi siswa untuk aktif bertanya dan guru kesulitan membuat siswa untuk menyampaikan kesimpulan secara mandiri. Solusi untuk kendala tersebuta yaitu guru memberikan kesempatan siswa untuk menanyakan hal yang belum jelas dan guru lebih memberikan waktu berpikir kepada siswa untuk berani menyimpulkan materi pembelajaran. Kata Kunci: VAK, Multimedia, Pembelajaran, IPS